An Estimation of Technical Efficiency and Economies of Scale and Scope in the UK Property-Liability Insurance Industry ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂ¢ÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂÃÂ Use the Parametric Approach - WANG, YUNYAO (2008)
The paper examines technical efficiency and economies of scale and scope in the UK property-liability insurance industry over the sample period of 1985-2003 using stochastic cost frontier analysis. Stochastic frontier model for panel data are utilized to explore the relationships between firm size, technical efficiency, scale and scope economies. The estimate results indicate satisfactory overall technical efficiency, whereas a few firms of and above medium scale are significantly inefficient. It is noteworthy that specialist insurers are less than one fifth of the total number of property-liability firms in the market. Diversified insurers in the upper and second quartile of scale are more efficient compared to specialists. Evidence of scope economies exist within the majority of diversified firms, especially those below median size in the industry.